Omicron Variant Generates a Higher and More Sustained Viral Load in Nasopharynx and Saliva Than the Delta Variant of SARS-CoV-2 - Beathe K. Granerud; Thor Ueland; Andreas Lind; Arne Søraas; Børre Fevang; Anne Katrine Steffensen; Huda Al-Baldawi; Fridtjof Lund-Johansen; Pål Aukrust; Bente Halvorsen; Tuva B. Dahl; Susanne Dudman; et al. (Viruses, 2022)
The Omicron variant of SARS-CoV-2 spreads more easily than earlier variants, possibly as a result of a higher viral load in the upper respiratory tract and oral cavity. Hence, we investigated whether the Omicron variant generates a higher viral load than that of the Delta variant in saliva and nasopharynx. Both specimens were collected from 52 Omicron and 17 Delta cases at two time points one week apart and analyzed by qRT-PCR. Viral load was measured as 10 log RNA genome copies per 1000 human cells according to the WHO reference standard. We found that Omicron cases carried a higher viral load and had more sustained viral shedding compared to the Delta cases, especially in the nasopharynx.